Multiple Facets of Autophagy and the Emerging Role of Alkylphosphocholines as Autophagy Modulators - Kaleağasıoğlu, Ferda; Ali, Doaa M.; Berger, Martin R. (Frontiers in Pharmacology, 2020)
Autophagy is a highly conserved multistep process and functions as passage for degrading and recycling protein aggregates and defective organelles in eukaryotic cells. Based on the nature of these materials, their size and degradation rate, four types of autophagy have been described, i.e. chaperone mediated autophagy, microautophagy, macroautophagy, and selective autophagy. One of the major regulators of this process is mTOR, which inhibits the downstream pathway of autophagy following the activation of its complex 1 (mTORC1). Alkylphosphocholine (APC) derivatives represent a novel class of antineoplastic agents that inhibit the serine–threonine kinase Akt (i.e. protein kinase B), which mediates cell survival and cause cell cycle arrest. They induce autophagy through inhibition of the Akt/mTOR cascade. They interfere with phospholipid turnover and thus modify signaling chains, which start from the cell membrane and modulate PI3K/Akt/mTOR, Ras-Raf-MAPK/ERK and SAPK/JNK pathways. APCs include miltefosine, perifosine, and erufosine, which represent the first-, second- and third generation of this class, respectively. In a high fraction of human cancers, constitutively active oncoprotein Akt1 suppresses autophagy in vitro and in vivo. mTOR is a down-stream target for Akt, the activation of which suppresses autophagy. However, treatment with APC derivatives will lead to dephosphorylation (hence deactivation) of mTOR and thus induces autophagy. Autophagy is a double-edged sword and may result in chemotherapeutic resistance as well as cancer cell death when apoptotic pathways are inactive. APCs display differential autophagy induction capabilities in different cancer cell types. Therefore, autophagy-dependent cellular responses need to be well understood in order to improve the chemotherapeutic outcome.